Uso de sistemas de comunicação suplementar e alternativa na Educação Infantil: percepção do professor - Massaro, Munique [UNESP]; Deliberato, Débora [UNESP] (My University, 2013)
Augmentative and Alternative Communication Resources have proven to be helpful in the insertion of students with disabilities and complex communication needs into a variety of pedagogical activities and expand the skills and competencies of the teacher in the teaching-learning. The objective of this research was to identify the perception of teachers regarding the use of augmentative and alternative communication during an intervention program in Preschool. Participants were a special class of Preschool students with disabilities and severe communication complexity, along with their teacher and the researcher. For the development of this research, a Alternative Communication Program was applied. The teacher was provided with systematic guidance concerning language and communication. In a collaborative process, three children’s songs were selected according to the teacher’s pedagogical planning and adapted resources through Augmentative and Alternative Communication Systems. During the intervention program, assisted evaluations also took place immediately after the activities with the music. The data were collected in audio recordings. For data analysis, content analysis was carried out resulting in the outlining of themes and subthemes. Results indicated that the teacher identified that Augmentative and Alternative Communication Systems can to facilitate expression abilities of students with disabilities; that Augmentative and Alternative Communication Systems can be used by children in Preschool; and that resources adapted through augmentative and alternative communication systems should be in accordance with the specificities of students.

Os recursos de comunicação suplementar e alternativo podem inserir o aluno com deficiência e necessidades complexas de comunicação em diferentes atividades pedagógicas e ampliar as habilidades e as competências do professor no processo de ensino-aprendizagem. Assim, o objetivo da pesquisa foi identificar a percepção do professor a respeito do uso da comunicação suplementar e alternativa durante um programa de intervenção na Educação Infantil. Participaram uma classe especial da Educação Infantil que possui sete alunos com deficiência e necessidades complexas de comunicação, a professora e a pesquisadora. Para o desenvolvimento da pesquisa, aplicou-se um programa de comunicação alternativa. Ocorreram orientações sistemáticas à professora, a respeito de linguagem e comunicação. Em um processo colaborativo, foram selecionadas três canções infantis, conforme o planejamento pedagógico da professora e os recursos foram adaptados por meio de sistemas de comunicação suplementares e alternativos. Durante o programa de intervenção, também foram realizadas avaliações assistidas imediatamente após as atividades com a música. Os dados da pesquisa foram coletados por meio de gravação em áudio. Para análise dos dados, foi realizada análise de conteúdo, estabelecendo temas e subtemas. Os resultados indicaram que a professora identificou que sistemas de comunicação suplementares e alternativos podem favorecer as habilidades de expressão dos alunos com deficiência; que os sistemas de comunicação suplementares e alternativos podem ser utilizados por crianças na Educação Infantil; e que recursos adaptados por meio dos sistemas suplementares e alternativos de comunicação devem estar de acordo com as especificidades dos alunos.
Use of Augmentative and Alternative Communication Systems in Preschool: teacher perceptions
Keywords: EDUCAÇÃO ESPECIAL; INCLUSÃO; ACESSIBILIDADE COMUNICATIVA; COMUNICAÇÃO ALTERNATIVA